(3QSGdI aj GdJTQjMs - (3Ydj Hf EHQGgje GdcaQWCHjs
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdeYHhO GdeWgQ ef GdYOe Edi GdhLhO NGdb GdEfSGf ef LhgQ GdCQcGf GdLGeY ajg Ydi UZQg eG ai GdYGde EdG YXe Ydi cHQg Ndbg s
(3BNQgG (B:s
(3dCfg dG jecf Cf jba Ydi JOHjQ Gddg ddYGde djbJai CKGQg ai CLRGA GdehVhY ddbhd EdG ef GdadSaI ef ZjQ Pdc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs